POLITIK PENDIDIKAN ISLAM DI SUMATERA UTARA PERAN JAMI’ATUL AL-WASHLIYAH - Ependi, Rustam (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2019)
Education is a political sphere that stands and operates based on political decisions; no exception whether it is a government or private educational institution. Jami'atul Washliyah is one of the organizations that nuances religioous and cannot be separated from the political dimension in the context of education. This paper is based on historical studies through library research. The Islamic organization known as Jami'atul al-Washilyah where its preaching especially in North Sumatra played a very important role mainly through education. One strategy used to spread Islam (Islamic da'wah) uses the term "zending" which is generally used by invaders in spreading their religion, Christianity. So in the context of Islamic da'wah using the term "Zending Islam" was first used by al-Washliyah as its da'wah strategy in the midst of a predominantly non-Muslim population such as in Porsea.